2011
DOI: 10.1007/s00595-010-4230-3
|View full text |Cite
|
Sign up to set email alerts
|

Is routine calcium supplementation necessary in patients undergoing total thyroidectomy plus neck dissection?

Abstract: Symptomatic hypocalcemia develops within 3 days after surgery. An sCa level of less than 1.81 mmol/l can predict symptomatic hypocalcemia. Routine calcium supplements will not be necessary if the sCa level is higher than 1.81 mmol/l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…The following biochemical factors were not found to be associated with hypocalcaemia in any of the included studies: postoperative calcitonin, preoperative creatinine, preoperative cholesterol, preoperative albumin, preoperative thyroid hormone, preoperative phosphate and preoperative magnesium.…”
Section: Resultsmentioning
confidence: 86%
“…The following biochemical factors were not found to be associated with hypocalcaemia in any of the included studies: postoperative calcitonin, preoperative creatinine, preoperative cholesterol, preoperative albumin, preoperative thyroid hormone, preoperative phosphate and preoperative magnesium.…”
Section: Resultsmentioning
confidence: 86%
“…In addition, the clinical value of postoperative phosphate in predicting transient hypocalcaemia is unclear, as the changes in phosphate seem to occur after the first postoperative day.…”
mentioning
confidence: 99%
“…Our results showed that preoperative serum magnesium levels were significantly higher in PoSH group compared to controls and postoperative serum magnesium levels were not different in the two groups. Other studies have also found no association between postoperative serum magnesium and post-thyroidectomy hypocalcaemia (25,26). In contrast, Brophy et al found similar preoperative serum magnesium levels in both groups, but lower postoperative serum magnesium levels in patients with PoSH (21).…”
Section: Discussionmentioning
confidence: 90%